Kevalidan Instrumen Authentic Assessment Untuk Mengukur Kemampuan Berpikir Kritis Peserta Didik Pada Problem Based Learning (PBL) Materi Hukum Newton Tentang Gerak (MAGNETON: Jurnal Inovasi Pembelajaran Fisika, 2025)
This study developed an authentic assessment instrument based on Problem-Based Learning (PBL) to measure students' critical thinking skills in Newton's laws of motion. We used Thiagarajan's 4D model (1974) to adapt the Research and Development (R&D) method, which includes the following stages: (1) Define (analysis of needs at SMAN 1 Sukoharjo showed that 62% of teachers did not have adequate critical thinking assessment instruments, (2) Design (development of a rubric based on Ennis' indicators, 1996), (3) Develop (expert validation and empirical testing), and (4) Disseminate (limited implementation). Validation by three experts (2 lecturers and 1 teacher) resulted in an average score of 82.48% (highly valid), with details as follows: construct aspect (83.33%), substance (78.02%), and language (86.10%). A pilot test on 35 students using Rasch model analysis (Ministeps 5.4.1) confirmed that 12 items met validity criteria. The instrument has high reliability (Cronbach’s Alpha 0.81) and exceptional practicality (96.16% score based on teacher assessment). The uniqueness of this research lies in the integration of the PBL approach with an authentic assessment rubric structured according to problem-solving stages, as well as the use of Rasch analysis for empirical validation. These findings provide practical contributions for physics teachers in implementing 21st-century skills-based assessment while filling a gap in the literature on specific instruments for Newton's Law material.
Keywords: Authentic Assessment; critical thinking skills; problem-based learning